Mediating role of splitting in relation to attachment styles and shopping addiction - Allahvirdie Rezaieh, Sarah; Ghorbani, Nima; Farahani, Hojjatollah (Frontiers in Psychology, 2023)
Shopping can provide a sense of satisfaction and pleasure; however, if a person's excessive involvement in this behavior starts to negatively impact other aspects of their life, similar to other addictive behaviors like excessive internet use, gaming, and gambling, it may be classified as pathological. Given the lack of agreement regarding the classification of excessive shopping tendencies as a separate mental health condition or an addictive behavior, taking a socio-emotional approach to explore the psychological factors that precede this behavior, may offer a better comprehension of it. The purpose of this study was to examine the relationship between attachment styles and excessive shopping behavior, as well as to investigate the potential mediating effect of defense mechanisms like splitting on this relationship. Using convenience sampling, a group of 457 stock market employees (116 female, 341 male) between the ages of 24 and 60 were recruited. The researchers utilized a set of validated psychological questionnaires to assess the employees' attachment styles, shopping addiction, and splitting tendencies. The results obtained from both the mediation model and path analysis suggest that attachment styles do not have a direct relationship with shopping addiction. Nonetheless, the study supports the impact of insecure anxious and avoidant attachment styles on splitting. Furthermore, the findings confirm that splitting has a mediating effect on the relationship between attachment styles and splitting. The present study enhanced our comprehension of the subconscious mechanisms underlying shopping tendencies. Specifically, the findings suggest that excessive tendencies towards shopping can be considered a maladaptive response resulting from insecure attachment styles and the unconscious utilization of the splitting defense mechanism.